In critical condition : polemical essays on cognitive science and the philosophy of mind - Fodor, Jerry (The MIT Press, 1998)
In this book Jerry Fodor contrasts his views about the mind with those of a number of well-known philosophers and cognitive scientists, including John McDowell, Christopher Peacocke, Paul Churchland, Daniel Dennett, Paul Smolensky, and Richard Dawkins. Several of these essays are published here for the first time. The rest originated as book reviews in the Times Literary Supplement, the London Review of Books, or in journals of philosophy or psychology. The topics examined include cognitive architecture, the nature of concepts, and the status of Darwinism in psychology. Fodor constructs a version of the Representational Theory of Mind that blends Intentional Realism, Computational Reductionism, Nativism, and Semantic Atomism.